Understanding Managers' Moral Decision-Making - Kujala, Johanna (International journal of value-based management, 2003)
The paper discusses managers' moral decision-making based on analyses of managers' talk when they are facing a morally problematic situation. The qualitative data was collected by a survey questionnaire from Finnish top managers in large manufacturing companies. The research questions are: How managers construct good in their speech? How managers reason for a moral choice? Managers' reasoning is analysed by grouping the responses according to whether they agree or disagree with the presented moral dilemma, and by finding the cultural distinctions managers make in the responses. The analysis shows that ethical theories are used, if not explicitly, at least implicitly in managers' moral decision-making. Good is constructed in managers' speech by either referring to the consequences of an action, to certain moral norms or rules, or to the culturally accepted way of action. The content of the reasons for a moral choice varies depending on whether the response reflects disagreeing, agreeing or uncertain attitude towards the given moral dilemma.